THE INFLUENCE OF POST ONLINE LEARNING ON SOCIAL BEHAVIOR OF JUNIOR HIGH SCHOOL IN JAMBI CITY STUDENTS - Linanda, Elvira; Amanah, Siti; Gutji, Nelyahardi (Jurusan Bimbingan dan Konseling, 2024)
This research is motivated by the phenomenon of students showing changes in social behavior. One of the influences is the implementation of online learning methods. Some of these changes in social behavior include the lack of communication between classmates, indifference and indifference towards teachers when they pass each other, and a lack of concern for the social environment. This research aims to reveal the influence of post-online learning on students' social behavior at junior high school in Jambi City. This type of research is quantitative with a survey method. The data collection technique is using a questionnaire, and the sampling technique is using random sampling with a total sample of 165 students. To determine the validity of the instrument, validity and reliability tests are carried out. Meanwhile, data analysis techniques use the C formula, normality test, linearity test, and simple regression analysis assisted by the SPSS 26 program. The results showed that there was an influence after online learning on students' social behavior at a percentage of 30.7% or 0.307 with a Strong Enough classification. The teacher/school should provide direction on the implementation of online learning and coaching to always have good social behavior when face-to-face learning and online learning.